Intensity-modulated radiotherapy with simultaneous modulated accelerated boost technique and chemotherapy in patients with nasopharyngeal carcinoma - Fareed, Muhammad M (BioMed Central, 2013)
BACKGROUND: To present our experience of intensity-modulated radiotherapy (IMRT) with simultaneous modulated accelerated radiotherapy (SMART) boost technique in patients with nasopharyngeal carcinoma (NPC). METHODS: Sixty eight patients of NPC were treated between April 2006 and December 2011 including 45 males and 23 females with mean age of 46 (range 15–78). Stage distribution was; stage I 3, stage II 7, stage III 26 and stage IV 32. Among 45 (66.2%) evaluated patients for presence of Epstein-Barr virus (EBV), 40 (88.8%) were positive for EBV. Median radiation doses delivered to gross tumor volume (GTV) and positive neck nodes were 66–70 Gy, 63 Gy to clinical target volume (CTV) and 50.4 Gy to clinically negative neck. In addition 56 (82.4%) patients with bulky tumors (T4/N2+) received neoadjuvant chemotherapy 2–3 cycles (Cisplatin/Docetaxel or Cisplatin/Epirubicin or Cisplatin/5 Flourouracil). Concurrent chemotherapy with radiation was weekly Cisplatin 40 mg/m(2) (40 patients) or Cisplatin 100 mg/m(2) (28 patients). RESULTS: With a median follow up of 20 months (range 3–43), one patient developed local recurrence, two experienced regional recurrences and distant failure was seen in 3 patients. Estimated 3 year disease free survival (DFS) was 94%. Three year DFS for patients with EBV was 100% as compared to 60% without EBV (p = 0.0009). Three year DFS for patients with undifferentiated histology was 98% as compared to 82% with other histologies (p = 0.02). Acute grade 3 toxicity was seen as 21 (30.9%) having G-III mucositis and 6 (8.8%) with G-III skin reactions. Late toxicity was minimal and loss of taste was seen in 3 patients (7.5%) at time of analysis. CONCLUSIONS: IMRT with SMART in combination with chemotherapy is feasible and effective in terms of both the clinical response and safety profile. EBV, histopathology and nodal involvement were found important prognostic factors for locoregional recurrence.